Maues, China, and the Replacement of the Indo-Greeks - Falk, Harry (Anabasis. Studia Classica et Orientalia, 2022)
Maues, known as the first so-called Scythian ruler within the Indo-Greek culture zone, ruled from Taxila during the first half of the first century BC. His realm included Kashmir, Hazara, parts of the western Panjab, and part of the Peshawar valley with Kohat in its south. These geographical limits are based on the numerous coin finds in the said areas. Coins of Maues, of the Indo-Greek Telephos, and the Chinese chronicle on Yin-mofu imply that Maues supplanted an Indo-Greek dynasty not by defeating its armies, nor by marrying one of their daughters, but by offering his troops as help against other Indo-Greeks and by plotting with a Chinese platoon to the disadvantage of the widow and the only son of the last local potentate in the area, Artemidorus.